2016
DOI: 10.1128/aem.04046-15
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Influenza A (H1N1) Virus on Stainless Steel Surfaces

Abstract: As annual influenza epidemics continue to cause significant morbidity and economic burden, an understanding of viral persistence and transmission is critical for public health officials and health care workers to better protect patients and their family members from infection. The infectivity and persistence of two influenza A (H1N1) virus strains (A/New Caledonia/20/1999 and A/Brisbane/59/2007) on stainless steel (SS) surfaces were evaluated using three different surface matrices (2% fetal bovine serum, 5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…In contrast, Firquet et al observed infectious Influenza A virus (strain H1N1 A/PR/8/34) on plastic petri dishes was inactivated after 5 days at RT [ 23 ]. Perry et al observed that two strains of Influenza A virus remained infective on steel after 7 days under various environmental conditions (18 °C + 20% RH, 25 °C + 20% RH, 18 °C + 35% RH, 25 °C + 35% RH, 18 °C + 55% RH, 25 °C + 55% RH) [ 45 ]. To examine the influence of light on the survival of Influenza A virus, Thompson et al surveyed five different strains on three materials (cotton, microfiber and stainless steel) in light and dark environment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Firquet et al observed infectious Influenza A virus (strain H1N1 A/PR/8/34) on plastic petri dishes was inactivated after 5 days at RT [ 23 ]. Perry et al observed that two strains of Influenza A virus remained infective on steel after 7 days under various environmental conditions (18 °C + 20% RH, 25 °C + 20% RH, 18 °C + 35% RH, 25 °C + 35% RH, 18 °C + 55% RH, 25 °C + 55% RH) [ 45 ]. To examine the influence of light on the survival of Influenza A virus, Thompson et al surveyed five different strains on three materials (cotton, microfiber and stainless steel) in light and dark environment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the virus was viable on plastic after 9 h, with a slightly greater reduction (4.2-log). On silver containing cloth, soft toys and light switch material, Influenza A virus survived for more than 4 h and less than 9 h. And on J-cloth ® , window glass, telephone handset, kitchen work surface, computer keyboard, aluminum, pine, varnished and unvarnished oak, the virus was not detectable after 4 h. Greatorex [45]. To examine the influence of light on the survival of Influenza A virus, Thompson et al surveyed five different strains on three materials (cotton, microfiber and stainless steel) in light and dark environment [46].…”
Section: Influenza a Virusmentioning
confidence: 99%
“…Ultimately, it is important to understand the extent of inactivation when viruses are deposited in the actual matrices found on N95 respirators. The limited studies that have compared artificial and more realistic deposition matrices (e.g., human saliva) suggest that laboratory-made solutions (e.g., cell culture media or artificial saliva) are not fully representative of respiratory droplets and aerosols ( 29 , 34 , 35 , 56 ). For this reason, we tested human saliva as a more realistic deposition solution and compared the results to those obtained with the other deposition solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have suggested that the physical environment plays a prominent role in respiratory disease transmission. Influenza A H1N1 has been shown to survive on common surfaces for up to 17 days, remaining infectious for at least a week [14, 15]. Other respiratory pathogens such as coronavirus 229E remain infectious for at least 5 days on a variety of materials including ceramics, rubber and glass [16].…”
Section: Introductionmentioning
confidence: 99%